Even if the sky is falling - McCoy, Taj; McCoy, Taj; Heron, Farah; Clarke, Lane; Reid, Charish; Smith, Sarah, 1985-; Williams, Denise, 1982- (Canary Street Press, 2023)
"When an international warning siren accidentally goes off, convincing everyone that a meteor shower may just be the end of life as they know it, six couples--friends, exes, crushes and rivals--must take shelter. Inhibitions are abandoned, confessions are made and love blossoms, but what happens when the world doesn't end? Filled with humor, heat and hope, this riveting collection of interconnected multicultural stories by acclaimed authors Lane Clarke, Farah Heron, Taj McCoy, Charish Reid, Sarah Smith and Denise Williams beautifully explores the secrets we carry with us--and the joy we discover when we let go and reach for the stars."--Provided by publisher.